МЕТОДЫ ПОВЫШЕНИЯ ЭФФЕКТИВНОСТИ ИМПУЛЬСНОГО ПРЕОБРАЗОВАНИЯ ПЕРЕМЕННОГО НАПРЯЖЕНИЯ - Голубев, В.В. (Інститут електродинаміки НАН України, Київ, 2013)
In work the schematic and algorithmic methods of improvement of quality of entrance and output energy of pulse converters of alternating current are considered. For converters, workings on the active-inductive loading without entrance and output filters, crucial importance get quality of entrance and output currents. The schematics and the algorithms of control allowing it is optimum to combine requirements to quality of energy and to the weight-overall indexes are resulted. The methods of simultaneous change of duty cycle and frequency of regulation for a receipt unchanging at set level or higher quality of output current in a wide range of regulation of a output voltage are received. The complicated algorithms of management at the increased frequencies of regulation allow to reduce number switchings and losses to them without decrease in quality of entrance and output energy. References 10, figures 10.